Trademark Registration Profile of Auditing Service Providers in Brazil - Dias, Leonôra Virginia de Jesus; Santos, José Wendel dos; Magnani, Vinícius Medeiros (Revista Contabilidade & Inovação, 2025)
This study aims to analyze the profile of trademark registration requests made by audit service providers at the National Institute of Industrial Property (INPI), to understand the importance of this intangible asset in consolidating professional reputation in the market. A quantitative exploratory approach was adopted, based on the analysis of structured data extracted from the INPI trademark database. Data were collected for the period from 2011 to 2021 on trademark registration applications filed by individuals and legal entities linked to the auditing activity. The data were processed and analyzed using descriptive statistics. The variables examined included the Nice Class, type of trademark (nominative, figurative, mixed), filing date, and application status. The results revealed a predominance of legal entities as applicants (80%), with a concentration in Class 35 (administrative services). Mixed trademarks, which combine nominative and figurative elements, represented the majority of the sample (138 applications). This study highlights the importance of trademark registration in differentiating and protecting the corporate identity of auditors. In addition, it highlights the need to invest in training professionals specialized in the area. The complexity of the registration process and the constant evolution of legislation require that audit professionals remain up to date on legal requirements and best practices to ensure the effective protection of their brands.